Banking System Adjustment to Regulatory Capital Requirements - Ivica Klinac; Roberto Ercegovac (Croatian Economic Survey, 2018)
The main objective of this paper is to explore the adjustment of bank business activities to new regulatory capital requests using panel data analyses of the European banking system. The research hypothesis assumes that the increase in capital requirements affects the banks’ balance sheet adjustment and bank lending to the non-financial sector. The banks can maintain the higher regulatory capital ratio by increasing the volume of share capital or by decreasing the risk-weighted assets and bank lending activities. The high equity premium upon a new equity issue due to asymmetric information about the bank’s net worth discourages the current shareholder to issue additional capital, which has resulted in bank lending constraints and has increased non-risk bank assets. Banks’ response to new capital requirements can announce a long-term negative impact to real economy and bank depending borrowers. The model of empirical analysis of the banking sector adjustment to new capital requirements will be demonstrated on the sample of publicly listed banking firms in the European Union in the period 2000–2016 using dynamic panel-data estimation with the Generalized Method of Moments (GMM) in one-step.